2016
DOI: 10.1080/1369183x.2016.1139445
|View full text |Cite
|
Sign up to set email alerts
|

The role of corruption in reintegration: experiences of Iraqi Kurds upon return from Europe

Abstract: This article examines how corruption affects reintegration. The literature on return and reintegration shows that return migrants often struggle to adjust and adapt to life in their place of origin because that environment can be very different from what they grew accustomed to abroad. One stark difference is the prevalence and meaning of corruption. In many sending countries that migrants come from and then return to, corruption is endemic. By contrast, in many receiving countries that migrants go to and retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Similarly, Paasche’s study of Iraqi returnees found that they had adapted to a less corrupt society abroad and that the corruption in the home country therefore made them feel a sense of alienation from their home country. Paasche describes how the returnees considered corruption a major challenge to their own reintegration both psychosocially, by creating a feeling of insecurity and hindering the development of a sense of belonging in their home country, and economically, by obstructing entrepreneurship and producing relative deprivation [ 41 ]. Corruption has thus been shown to create complications for return migrants other than the Bosnians in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Paasche’s study of Iraqi returnees found that they had adapted to a less corrupt society abroad and that the corruption in the home country therefore made them feel a sense of alienation from their home country. Paasche describes how the returnees considered corruption a major challenge to their own reintegration both psychosocially, by creating a feeling of insecurity and hindering the development of a sense of belonging in their home country, and economically, by obstructing entrepreneurship and producing relative deprivation [ 41 ]. Corruption has thus been shown to create complications for return migrants other than the Bosnians in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation has been described by Paasche, who studied the return of Iraqi refugees. Paasche reports that Iraqi refugees who had returned from Norway and the United Kingdom were more frequently asked for bribes than was the case for those who had never fled from Iraq, and they were also asked for larger bribes than individuals who had not been refugees abroad [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies point towards returnees' negative experiences with corruption and local power relations, feelings of frustration and disappointment in the homeland context (Emanuelsson, 2008). This is also the case with Iraqi Kurdish return migration, as shown by Emanuelsson (2008) and more recently by Paasche (2016aPaasche ( , 2016b. For instance, Paasche (2016b: 129) has found that, in many returnee narratives, KRG's ruling elites appeared as above the rule of law and ruling the region through neo-patrimonial patronage.…”
Section: Challenges Of 'Diasporic Homecomings'mentioning
confidence: 87%
“…Table 1 shows that reintegration is mainly measured through economic ( n = 26) and social ( n = 16) dimensions. To a lesser extent, psycho‐social (measured through returnees' psycho‐social well‐being and feelings of self‐worth) and political dimensions (measured using returnees' perceptions of safety, trust in the government and access to justice and citizenship rights) are also mentioned (Cherti et al ., 2013; Brisbois et al ., 2016; Mercier et al ., 2016; Paasche, 2016; Flahaux, 2017).…”
Section: Introductionmentioning
confidence: 99%